Knowledge, attitude and practice towards mental health illnesses in an urban community in West Bengal: a community based study - Bagchi, Abantika; Sarkar, Paramita; Basu, Rivu (International Journal Of Community Medicine And Public Health, 2020)
Background: Mental illness is a significant challenge and becoming more relevant in today’s fast paced world. According to WHO, mental health is “a state of well-being in which the individual realizes his or her own abilities, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to his or her community”. The aim of the present study was to assess the knowledge about mental illness and attitude and practice of the public toward people with mental illness. Methods: An observational, descriptive study with cross-sectional design was done among 200 adults of Bagh bazar slum, urban field practice area of department of Community Medicine, R. G. Kar Medical College and Hospital, Kolkata, West Bengal, India in May 2019 with a predesigned, pretested schedule. Results: Only 2.5% says that they are willing to live with a people with mental illness and only 1% has actually done so. Health-care seeking behavior shows that 54.5% will go to a general practitioner in case of any mental illness though only 2.5% believed that people with severe mental illness can fully recover. Attitude toward mental illness showed mixed picture as also in knowledge. Conclusions: Health education and public awareness regarding mental illness can decrease the stigma, prejudice; discrimination attached with it and improves help-seeking behaviour of the community. This study provides insights into the cognitive and affective aspect of mental illness among adult population of the study area. It will also help in implementing better policies for increasing public awareness regarding mental illness.